Comparative Short-Term Clinical Outcomes of Mediastinum Tumor Excision Performed by Conventional VATS and Single-Port VATS: Is It Worthwhile?. Issue 45 (November 2015) - Wu, Ching-Feng; Gonzalez-Rivas, Diego; Wen, Chih-Tsung; Liu, Yun-Hen; Wu, Yi-Cheng; Chao, Yin-Kai; Hsieh, Ming-Ju; Wu, Ching-Yang; Chen, Wei-Hsun
Abstract : Abstract: Single-port video-assisted thoracoscopic surgery (VATS) has been widely applied recently. However, there are still only few reports describing its use in mediastinum tumor resection. We present the technique of single-port video-assisted thoracoscopic mediastinum tumor resection and compare it with conventional VATS with regard to short-term outcome. We retrospectively enrolled 105 patients who received mediastinum surgery in Chang Gung Memorial Hospital. Sixteen patients received sternotomy or thoracotomy, 29 patients received single-port VATS, and 60 patients received conventional VATS (3 ports). The operative time, blood loss, postoperation day 1 pain score, discharge day pain score, and postoperative hospital stay were compared. In order to establish a well balanced cohort study, we also use propensity scores match (1:1) to compare the short-term clinical outcome in 2 groups. No operative deaths occurred in this study. Single-port VATS was associated with shorter operative time, lower postoperation day 1 pain score, and shorter postoperation hospital stay in our cohort study ( P = 0.001, <0.001, and 0.039), and propensity scores matched cohort study ( P = 0.003, <0.001, and <0.001). Single-port VATS for mediastinum tumor appears to be a safe and promising technique with short-term outcome not inferior to conventional VATS in our cohort study. The long-term oncology outcome may require time and more enrolled patients to be further evaluated.